Analisis Bibliometrik Media Pembelajaran menggunakan VOSViewer - Layli Maydawati (Jurnal Pustaka Cendekia Pendidikan, 2024)
Instructional media are essential to the elementary school teaching and learning process, accommodating each student's different learning styles and abilities. This study aims to examine the development of instructional media research in elementary schools using a computational bibliometric analysis method through VOSViewer. Publication data from Google Scholar-indexed journals were collected through a search on the Publish or Perish application. A search for keywords in research titles and abstracts resulted in 211 relevant articles published in 2013-2022. The analysis showed that the number of research articles on instructional media in elementary schools increased every year. From 2013 to 2019, research on instructional media in elementary schools focused on developing media in certain grades and subjects. Whereas, between 2019 and 2020, research on instructional media in elementary schools focused on the influence of learning media, including effectiveness, learning outcomes, learning innovations, and their influence on classroom learning by teachers. In 2020-2022, research on this topic focused more on online-based learning media due to the Covid-19 pandemic. Thus, many studies discussed the types of online instructional media in elementary schools, such as Powtoon, Android, videos, images, and interactive instructional media that can be accessed from home.